Post-tenure Review at U.S. Medical Schools. (December 2016) - Bunton, Sarah A.; Walling, Anne; Durham, Dianne
Abstract : Purpose: To assess post-tenure review policies at U.S. medical schools by examining how prevalent post-tenure review is, what models of post-tenure review are employed, and what outcomes result from post-tenure review processes. Method: In late 2014, a Web-based survey was sent to the associate dean for faculty affairs (or equivalent) at each U.S. medical school accredited by the Liaison Committee on Medical Education (N = 141). The survey addressed elements of post-tenure review policies, including whether a policy was in place, the frequency of the review, and the review outcomes. Descriptive statistics were calculated. Results: Of the 94 responding schools with a tenure system, 39 (41%) had an established post-tenure review policy. Although these policies showed great variability across schools in duration, having been in place from 1 to 50 years, 12 (31%) were established within the last 5 years. The outcomes of post-tenure review also varied. Superior performance ratings generally resulted in notations in the faculty member's personnel file and notifications to school leadership. Conversely, when a faculty member received an unsatisfactory rating, a remediation or development plan was sometimes required. Conclusions: At least 40% of medical schools with a tenure system have post-tenure review, and it is becoming more common. These findings about the prevalence and use of post-tenure review across institutions can assist medical school leaders as they strive to shape policies to facilitate faculty engagement and productivity. They also can provide the foundation for future evaluative studies on the effectiveness, outcomes, and impact of post-tenure review.